Burkholderia pseudomallei Triggers Altered Inflammatory Profiles in a Whole-Blood Model of Type 2 Diabetes-Melioidosis Comorbidity - Morris, Jodie (American Society for Microbiology, 2012)
Melioidosis is a potentially fatal disease caused by the bacterium Burkholderia pseudomallei. Type 2 diabetes (T2D) is the most common comorbidity associated with melioidosis. B. pseudomallei isolates from melioidosis patients with T2D are less virulent in animal models than those from patients with melioidosis and no identifiable risk factors. We developed an ex vivo whole-blood assay as a tool for comparison of early inflammatory profiles generated by T2D and nondiabetic (ND) individuals in response to a B. pseudomallei strain of low virulence. Peripheral blood from individuals with T2D, with either poorly controlled glycemia (PC-T2D [n = 6]) or well-controlled glycemia (WC-T2D [n = 8]), and healthy ND (n = 13) individuals was stimulated with B. pseudomallei. Oxidative burst, myeloperoxidase (MPO) release, expression of pathogen recognition receptors (TLR2, TLR4, and CD14), and activation markers (CD11b and HLA-DR) were measured on polymorphonuclear (PMN) leukocytes and monocytes. Concentrations of plasma inflammatory cytokine (interleukin-6 [IL-6], IL-12p70, tumor necrosis factor alpha [TNF-α], monocyte chemoattractant protein 1 [MCP-1], IL-8, IL-1β, and IL-10) were also determined. Following stimulation, oxidative burst and MPO levels were significantly elevated in blood from PC-T2D subjects compared to controls. Differences were also observed in expression of Toll-like receptor 2 (TLR2), CD14, and CD11b on phagocytes from T2D and ND individuals. Levels of IL-12p70, MCP-1, and IL-8 were significantly elevated in blood from PC-T2D subjects compared to ND individuals. Notably, differential inflammatory responses of PC-T2D, WC-T2D, and ND individuals to B. pseudomallei occur independently of bacterial load and confirm the efficacy of this model of T2D-melioidosis comorbidity as a tool for investigation of dysregulated PMN and monocyte responses to B. pseudomallei underlying susceptibility of T2D individuals to melioidosis.